Period variation of an eclipsing binary system BQ Ari. Issue 1 (1st January 2023) - Rattanamala, R; Komonjinda, S; Awiphan, S; Wutsang, S; Sappankum, P; Deesuan, L
Abstract: This study was aimed to study the period variation of the eclipsing binary BQ Ari. The system was observed from Thai Robotic Telescope at Spring Brook Observatory (TRT-SBO) between 2019 and 2020, Regional Observatory for Public, Chachoengsao (ROP-CCO) in 2021, and Transiting Exoplanet Survey Satellite (TESS) in Sector 42 and 43. The data obtained were used to create the light curves in each wavelength and compute the times of minima. As the result, we receive 311 time of minima. We combined the time of minima from the previously published with our values to calculate the O − C diagram. The O − C diagram shown the period variation with a period about 6-8 years and amplitude about 0.0020 days. The possibility of the period variation of BQ Ari may be due to the third body component with the mass of 0.0948 M ⊙ (M dwarf) and the orbital separation ( a 3 sin i ) around 3.96 AU.